Therapeutic Potential of Melatonin: Multifaceted Applications in Muscle Health, Metabolic Disorders and Cardiovascular Disease - Dydyk, Martyna; Wójcik, Jakub; Błaszczak, Ewa; Malinowski, Piotr; Kopczyńska, Urszula; Kopczyński, Cezary; Gurdak, Kinga; Michalska, Martyna; Małachowski, Aleksander; Zając, Aleksandra (Quality in Sport, 2024)
Melatonin, a hormone primarily synthesized by the pineal gland, is traditionally associated with the regulation of circadian rhythms. However, recent research has unveiled its broad spectrum of biological effects, positioning it as a valuable therapeutic agent in diverse health contexts. Known for its potent antioxidant and anti-inflammatory properties, melatonin plays a crucial role in maintaining homeostasis and protecting cellular integrity. This review explores melatonin’s therapeutic applications across multiple medical domains, including muscle health, metabolic disorders, chronic pain management, and cardiovascular health. In muscle health, melatonin facilitates muscle hypertrophy and regeneration by mitigating oxidative stress and enhancing the activity of satellite cells responsible for muscle repair. This action is particularly beneficial for individuals undergoing intense physical exertion, recovering from injuries, or combating age-related muscle. In metabolic disorders, such as type 2 diabetes, melatonin improves insulin sensitivity and reduces cellular oxidative damage, which supports beta-cell function and glucose regulation, potentially minimizing diabetes-related complications. Furthermore, in fibromyalgia - a condition marked by widespread pain and sleep disturbances - melatonin has demonstrated efficacy in alleviating pain and improving sleep quality, thus enhancing the overall quality of life for patients. In cardiovascular health, melatonin has shown promise in preventing and managing heart failure by reducing oxidative damage, modulating inflammatory pathways, and supporting endothelial function, which collectively contribute to improved cardiac health and reduced disease progression. This comprehensive review underscores melatonin’s emerging role as an integrative therapeutic agent in modern medicine.